О работе Порфмийской экспедиции ИА НАНУ— ИИМК РАН в 2009 г. - Вахтина, М.Ю.; Сон, Н.А.; Столяренко, П.Г. (Археологічні дослідження в Україні, 2010)
Results of the research of the Hellenistic fortifications in the north-eastern part of Porphmium city are presented, as well as the results of the protective work at the area of necropolis to the west from the city where two Hellenistic crypts and a ground grave were discovered.